SIMULATION MODEL OF MAKING SOCIO-ECO-ECONOMIC DEVELOPMENT PROGRAM FOR SOUTHERN RUSSIA - Alla Vasilyevna Temirkanova (Advanced Engineering Research, 2012)
The development of the conceptual approaches to the justification of the eco-economic imperatives of the sustainable socio-eco-ecological regional system is particularly relevant in the context of the transformation intensification in the modern macroeconomics and the increasing significance of the environmental factor. The economy management efficiency goes up through the development of additional tooling, principles and factors, and the increased instrument value claims target selectivity, tension, and application areas. The socio-eco-ecological regional model including a package of active innovation processes is the most promising for various offers for the development of the regional policy. The program generation of the socio-eco-ecological development of the southern Russia is analyzed. Both quantitative indices and qualitative characteristics of the macroeconomic situation in the south of Russia are considered. On their basis, the socio-eco-ecological development of the region can be projected. Potential scenarios of the development of the health resort and tourist complex, and of the region at large: inertia and investment — are presented.